Overcoming TKI resistance in fusion-driven NSCLC: New generation inhibitors and rationale for combination strategies (2020)
During the last several years, multiple gene rearrangements with oncogenic potential have been described in NSCLC, identifying specific clinic-pathological subgroups of patients that benefit from a targeted therapeutic approach, including anaplastic lymphoma kinase (ALK), c-ros protooncogene 1 (ROS1) and,more recently, REarranged during Transfection (RET) and neurotrophic tyrosine receptor kinases (NTRK) genes. Despite initial impressive antitumor activity, the use of targeted therapies in oncogene-addicted NSCLC subgroups is invariably associated with the development of acquired resistance through multiple mechanisms that can include both on-target and off-target mechanisms. However, the process of acquired resistance is a rapidly evolving clinical scenario that constantly evolves under the selective pressure of tyrosine kinase inhibitors. The development of increasingly higher selective and potent inhibitors, traditionally used to overcome resistance to first generation inhibitors, is associated with the development of novel mechanisms of resistance that encompass complex resistance mutations, highly recalcitrant to available TKIs, and bypass track mechanisms. Herein, we provide a comprehensive overview on the therapeutic strategies for overcoming acquired resistance to tyrosine kinase inhibitors (TKIs) targeting the most well-established oncogenic gene fusions in advanced NSCLC, including ALK, ROS1, RET, and NTRK rearrangements.